Cellular Mechanism of Myelination in the Central Nervous System - De Robertis, Eduardo (The Rockefeller University Press, 1958)
A study of myelination with electron microscopy has been carried out on the spinal cord of young rats and cats. In longitudinal and transverse sections the intimate relationship of the growing axons with the oligodendrocytes was observed. Early naked axons appear to be embedded within the cytoplasm and processes of the oligodendrocytes from which they are limited only by the intimately apposed membranes of both elements (axon-oligocytic membrane). In a transverse section several axons are observed to be in a single oligodendrocyte. The process of myelination consists in the laying down, within the cytoplasm of the oligodendrocyte and around the axon, of concentric membranous myelin layers. The first of these layers is deposited at a certain distance (200 to 600 A or more) from the axon-oligocytic membrane. This and all the other subsequently formed membranes have higher electron density and are apparently formed by the coalescence and fusion of vesicles (of 200 to 800 A) and membranes found in large amounts within the cytoplasm of the oligodendrocytes. At an early stage the myelin layers may be discontinuous and some vesicular material may even be trapped among them or between the myelin proper and the axon-oligocytic membrane. Then, when the 8th to 10th layer is deposited, the complete coalescence and alignment of the lamellae leads to the characteristic orderly multilayered organization of the myelin sheath. Myelination in the central nervous system appears to be a process of membrane synthesis within the cytoplasm of the oligodendrocyte and not a result of the wrapping of the plasma membranes as postulated in Geren's hypothesis for the peripheral nerve fibers. The possible participation of Schwann cell cytoplasm in peripheral myelination is now being investigated.